2016
DOI: 10.1038/srep20313
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Core/Shell-like NiCo2O4-Decorated MWCNTs and its Excellent Electrocatalytic Activity for Methanol Oxidation

Abstract: The design and development of an economic and highly active non-precious electrocatalyst for methanol electrooxidation is challenging due to expensiveness of the precursors as well as processes and non-ecofriendliness. In this study, a facile preparation of core-shell-like NiCo2O4 decorated MWCNTs based on a dry synthesis technique was proposed. The synthesized NiCo2O4/MWCNTs were characterized by infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, X-ray diffraction, and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Apparently, the HRTEM image of the composite shows the lattice spacing of 0.47 and 0.24 nm, which correspond with the interplanar spacing of NiCo 2 O 4 (111) and (311) planes, respectively . These results are similar to that of the bare NiCo 2 O 4 (Figure S1D‐F) and consistent with its d‐space in XRD consequences, indicating the polycrystalline state of the sample …”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Apparently, the HRTEM image of the composite shows the lattice spacing of 0.47 and 0.24 nm, which correspond with the interplanar spacing of NiCo 2 O 4 (111) and (311) planes, respectively . These results are similar to that of the bare NiCo 2 O 4 (Figure S1D‐F) and consistent with its d‐space in XRD consequences, indicating the polycrystalline state of the sample …”
Section: Resultssupporting
confidence: 75%
“…31 These results are similar to that of the bare NiCo 2 O 4 (Figure S1D-F) and consistent with its d-space in XRD consequences, indicating the polycrystalline state of the sample. 21 The valence states of the NiCo 2 O 4 /CTBs composite are characterized by X-ray photoelectron spectroscopy (XPS) measurement. The full XPS spectra of the materials are presented in Figure 2A (Table S1), the ratio between Ni and Co is about 1:2, so we can further confirm that the successful preparation of NiCo 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a strategy to combine both NiO and Co 3 O 4 resulted in the high electrocatalytic efficiency than their individual counterparts. For example, NiCo 2 O 4 exhibits excellent electrochemical activity due to higher electronic conductivity than either NiO or Co 3 O 4 [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…Astonishing physicochemical properties such as elegant morphology, stability and huge specific surface make graphene nanocomposites highly suitable for the heterogeneous catalysis 16 . Particularly, mechanochemically prepared carbon nanocomposites showed enhanced catalytic performance which is mainly due to the better metal-support interaction [17][18][19][20] . For instance, inert RuO 2 -nanoparticles were tuned to highly efficient catalyst by decorating it onto single-walled carbon nanotubes (SWCNTs) by a simple 'dry synthesis' 19 .…”
mentioning
confidence: 99%